2012
DOI: 10.1063/1.4736566
|View full text |Cite
|
Sign up to set email alerts
|

Minimal energy control of a nanoelectromechanical memory element

Abstract: The Pontryagin minimal energy control approach has been applied to minimise the switching energy in a nanoelectromechanical memory system and to characterise global stability of the oscillatory states of the bistable memory element. A comparison of two previously experimentally determined pulse-type control signals with Pontryagin control function has been performed and the superiority of the Pontryagin approach with regard to power consumption has been demonstrated. An analysis of global stability shows how v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Micro and nanoelectromechanical systems (MEMS and NEMS) have increasingly attracted considerable interest due to their small size, batch-fabrication, high reliability, and low power consumption. Therefore, M/NEMS were proposed in the past few decades for numerous potential applications including gas/mass sensing [1][2][3], filters [4][5][6][7] , memory devices [8][9][10], logic devices [11][12][13], and gyroscopes [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Micro and nanoelectromechanical systems (MEMS and NEMS) have increasingly attracted considerable interest due to their small size, batch-fabrication, high reliability, and low power consumption. Therefore, M/NEMS were proposed in the past few decades for numerous potential applications including gas/mass sensing [1][2][3], filters [4][5][6][7] , memory devices [8][9][10], logic devices [11][12][13], and gyroscopes [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…There have been attempts to exploit nonlinearity rather than avoiding it. Bistability and jump phenomena were used to enhance noise squeezing 24 , to enlarge the bandwidth of energy harvesters [25][26][27][28] , to improve mass detection 29 , to reduce the sensitivity of a resonator to the phase of the drive 7 and to develop new mechanical memory devices 30,31 . Superharmonic excitation and internal resonances were employed to improve stability properties of resonators 32 and time keeping devices 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Microelectromechanical systems or nanoelectromechanical systems (MEMS or NEMS) resonators have been developed for use as filters, frequency references, and sensor elements [1]. Recently, significant research has focused on mechanical computation based on MEMS or NEMS resonators [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Some studies have shown that a single mechanical resonator can be used as a mechanical 1-bit memory [2,3,5,7,8,[11][12][13]15] or as mechanical logic gates [6,9,10].…”
mentioning
confidence: 99%
“…Recently, significant research has focused on mechanical computation based on MEMS or NEMS resonators [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Some studies have shown that a single mechanical resonator can be used as a mechanical 1-bit memory [2,3,5,7,8,[11][12][13]15] or as mechanical logic gates [6,9,10]. Recently, multifunctional operation has been demonstrated in the form of a shift-register and a controlled NOT gate made from a single mechanical resonator [17].…”
mentioning
confidence: 99%